“Hiding In Plain Sight” Chronic Kidney Disease and Potential Consequences of the Proinflammatory State: Hemodialysis Catheter-Related Masses - Rozich, M.D., Ph.D., John D.; Rozich, M.S., Jacob J.; Rozich, M.D, Noah S. (International Journal of Innovative Research in Medical Science, 2018)
Multiple observational and experimental data support that chronic kidney disease (CKD) represents a “proinflammatory” state. These findings link this disordered inflammation and immunity to increased adverse cardiovascular (CV) events present in CKD through their role in atherosclerosis, but mechanisms of activation, recruitment and propagation remain unclear. Accordingly, the present effort reviewed the common use of indwelling hemodialysis catheters as a potential inflammatory trigger and immuno-amplifying variable. Hemodialysis intravenous catheters are routinely used to provide essential functional vascular access for patients requiring emergent or urgent hemodialysis. Numerous observations report that even within hours to days after insertion, a fibrin-thrombin-cellular matrix often forms around the catheter. This catheter associated “biomass” is so common it is usually thought to be clinically silent. But intravenous masses attached, or sheared off at catheter removal or remaining even after catheter explantation are recognized to provoke embolic and direct hemodynamic-related injury. Perhaps less recognized is that their formation, size and growth may be mechanistically linked to the heightened vascular immuno-reactivity found in CKD. Thus, vascular catheter placement or the associated reactive fibrin-thrombin-cellular matrix (or both) may directly contribute to pathologic CV immune-responsiveness in hemodialysis patients.